The Future of Healthcare: Patient-Owned Data and the Role of FHIR in Burden Reduction - Santosh Ratna Deepika Addagalla, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The healthcare landscape is undergoing a fundamental transformation through the shift to patient-owned data and FHIR-based interoperability. This transition places individuals at the center of their health information ecosystem, empowering them as active stewards rather than passive recipients of care documentation. FHIR serves as the technical foundation enabling this revolution through its RESTful architecture, resource-based data model, and integration with industry-standard security protocols. The implementation of FHIR standards addresses longstanding challenges of fragmented health records by enabling seamless information exchange between providers, patients, and digital applications. While organizations face significant implementation challenges including legacy system integration, data mapping complexity, varying implementation maturity, and security considerations, the benefits are substantial. Reduced administrative burden, enhanced clinical decision-making, improved patient safety, and new models of care delivery make this evolution compelling despite the hurdles. Emerging capabilities such as bulk data transfer, machine learning integration, and distributed consent management further extend FHIR's impact, pointing toward a future healthcare ecosystem that is more connected, transparent, and patient-centered.
Keywords: Consent Management; Healthcare Interoperability; Machine Learning; Patient Empowerment; Smart On FHIR